2021
DOI: 10.4038/sljmuok.v7i1.54
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Customer Intrinsic Value, Brand Trust and Consumer-Brand Relationship in the Life Insurance Industry: Scale Development and Validation

Abstract: This is the first study to comprehensively explore, develop and validate a scale for customer intrinsic value, brand trust and consumer-brand relationship behavior for the life insurance industry in Sri Lanka. This task was realized through an extensive literature review and discussions with academic experts and practitioners in the insurance field. A factor analysis was performed using the principal component analysis with Varimax rotation. The refined scales exhibit reliability, convergent validity, discrimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The design of the questionnaire was informed by known instruments and prior research on customer brand trust, as well as the variables that were uncovered. The development of the questionnaire was strengthened by previous studies that investigate the reliability, validity, and cross-context applicability of brand trust scales, thereby increasing the theoretical foundation of the research [47][48][49][50][51][52][53][54][55][56] as shown in figure 1, and variables as attached in supplement 1.…”
Section: Questionnairementioning
confidence: 99%
“…The design of the questionnaire was informed by known instruments and prior research on customer brand trust, as well as the variables that were uncovered. The development of the questionnaire was strengthened by previous studies that investigate the reliability, validity, and cross-context applicability of brand trust scales, thereby increasing the theoretical foundation of the research [47][48][49][50][51][52][53][54][55][56] as shown in figure 1, and variables as attached in supplement 1.…”
Section: Questionnairementioning
confidence: 99%